(untitled) (Journal of history, 2018)
The article describes the relationship between religion and state in the states of Western Europe. The most common types of this relationship are given the specific topics, systematized, and the corresponding state structures are presented as examples. There are three distinctive examples of traditionally recognized church-state relations in Western Europe: the Church as a predominantly national or state-owned confession; cooperative – cooperation between the church and the state, fixed in a special agreement; separatist – church’s separation from the state. The article begins with a general introduction to the topic and provides a comprehensive description of the relationship between the state and the church and the legislative documents used to regulate religious situation in countries. On the example of individual states the status of church, the state’s view on the church is examined. The contribution of public authorities and church officials to the regulation of religious situation is analyzed. Following the «Path to Europe» program implemented in our country between 2009 and 2011 in the field of cooperation with European countries, through the analysis and study of the models of European secular states, which have found solutions to a wide range of issues in the religious sphere, which has become a topical issue for our multinational country too, we can regulate the religious situation and develop effective mechanisms of governance.